International Humanitarian Law v International Human Rights Law: applicability in the crisis of Yemen - Alquhaly, Hiemyar; Salawati Mat Basir,; Saidatul Nadia Abd Aziz, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The United Nations (UN) has labelled Yemen's humanitarian crisis the worst in the world. Thousands of people have died in the ongoing war and from the outbreak of deadly diseases. Almost half Yemen's population desperately needs humanitarian aid, and millions have been internally displaced; hundreds of thousands of refugees have migrated to other countries. While children have been recruited as child soldiers, the illegal use of mines and cluster bombs has put at risk many more lives. International Human Rights Law (IHRL) requires the investigation of the arbitrary deprivation of life and others. The law dictates that the people responsible for violating any human rights or international humanitarian law must be held accountable for their crimes. In contrast, International Humanitarian Law (IHL) requires all states to have those people who are responsible for war crimes. This article discusses the applicability of both IHL and IHRL in the crisis in Yemen. Therefore, the first part of the paper presents a brief history of the problem in Yemen. The second part distinguishes between IHL and IHRL. The third part then deeply discusses in detail both IHL and IHRL and their possible applicability to the conflict in Yemen. Then lastly, the paper concludes by presenting how both IHL and IHRL could work to complement each other.